2020
DOI: 10.1186/s12875-020-1096-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation improves SIRT1, Irisin, and glucose indices in overweight or obese type 2 diabetic patients: a double-blind randomized placebo-controlled clinical trial

Abstract: Background: Vitamin D (VD) may increase sirtuin 1 (SIRT1) and subsequently PPAR-γ coactivator 1α (PGC-1α) and irisin levels and these improvements may reduce insulin resistance (IR). The aim was to assess the effects of vitamin D supplementation on SIRT1, irisin, and IR in overweight/obese type 2 diabetes (T2D) patients. Methods: Ninety T2D males and females were recruited as a clinical trial study (mean of age and body mass index (BMI) of intervention and placebo groups were 50.05 ± 10.17 and 50.36 ± 10.2 yrs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 46 publications
4
44
0
2
Order By: Relevance
“…In their work, Lemieux et al demonstrated that supplementation with 5000 IU daily of vitamin D for 6 months increased insulin sensitivity and pancreatic β-cell activity [ 48 ]. Other authors showed the benefits of supplementation with 50,000 IU/week of vitamin D for 8 weeks in patients with type 2 diabetes, with a reduction in glycosylated hemoglobin and an increase in sirtuin 1, which appears to be related to increased insulin secretion by pancreatic β-cells [ 50 ]. In their study on diabetic patients, Farrokhian et al also observed that an administration pattern of 50,000 IU every 2 weeks for 6 months reduces basal glycemia, increasing insulin sensitivity [ 51 ].…”
Section: Effect Of Vitamin D Supplementation On Metsmentioning
confidence: 99%
“…In their work, Lemieux et al demonstrated that supplementation with 5000 IU daily of vitamin D for 6 months increased insulin sensitivity and pancreatic β-cell activity [ 48 ]. Other authors showed the benefits of supplementation with 50,000 IU/week of vitamin D for 8 weeks in patients with type 2 diabetes, with a reduction in glycosylated hemoglobin and an increase in sirtuin 1, which appears to be related to increased insulin secretion by pancreatic β-cells [ 50 ]. In their study on diabetic patients, Farrokhian et al also observed that an administration pattern of 50,000 IU every 2 weeks for 6 months reduces basal glycemia, increasing insulin sensitivity [ 51 ].…”
Section: Effect Of Vitamin D Supplementation On Metsmentioning
confidence: 99%
“…In diabetic animal models, vitamin D increases irisin expression [160]. In overweight and obese patients, depletion of vitamin D is associated with worsened inflammatory state in obese [161], whereas vitamin D stimulus upregulated PGC-1α expression and consequently irisin secretion [162] Moreover, Safarpour et al have demonstrated that in obese and diabetic subjects vitamin D supplementation counteracts impaired insulin signaling and increased irisin signaling pathway [163]. Then, the relationship between irisin and vitamin D should be further investigated.…”
Section: Irisin: Nutritional Interventionsmentioning
confidence: 99%
“…following adjustment for changes of serum SIRT1 indicates a SIRT1-mediated effect of vitamin D on adiponectin secretion. Thus, vitamin D up-regulates SIRT1, as demonstrated in both animal model [51] and randomized clinical trial [21] and then SIRT1 in turn regulates adiponectin secretion. This nding is in accord with the report of regulation of adiponectin secretion by SIRT1 and endoplasmic reticulum oxidoreductase Ero1-Lα [52].…”
Section: Disappearance Of the Association Of Changes Of Serum 25(oh)dmentioning
confidence: 91%
“…The ameliorating effects of raising vitamin D status of subjects with T2D on glycemic status as well as parathyroid hormone, some antioxidative and in ammatory biomarkers have been already documented [10,13,14,[17][18][19]. Though the regulating effect of vitamin D on pancreatic β-cell function and insulin signaling has been described [20], there is evidence suggesting an indirect effect of vitamin D in T2D through other mediators including adiponectin and sirtuins [13,21].…”
Section: Introductionmentioning
confidence: 99%